Convergences and distances between writer Julio Cortázar and filmmaker Manuel Antín (Anclajes, 2024)
The epistolary relationship between Julio Cortázar (1914-1984) and Manuel Antín (1926) during the 1960s is an interesting case through which to study the relationship between literature and cinema –or vice versa– and, more specifically, the dialogue between two poetics that try, in their respective practices, to be at the forefront of the artistic process. In this process where enthusiasm and distancing progressively follow one another, this article argues that these artists’ poetics never fully agreed on any one point. Cortázar often insists on the need to innovate by building bridges with readers/viewers. This consisted of a cross between the imaginative freedom of surrealism, after overcoming its initial neo-romantic stage, and the ethical commitment that existentialism demanded, which grounds his novel Rayuela, written during those same years. The convergences they found through their interoceanic mail for the adaptations of the short stories “Cartas a mamá” and “Circe”, were diminished when Antín sent him his project and script to film Continuidad de los parques (1965), based on two other stories, which to the writer was a failure.
Keywords: Julio Cortázar; Manuel Antín; Argentine Literature; Film; Letters